2014
DOI: 10.1080/07294360.2014.973379
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous students' persistence in higher education in Australia: contextualising models of change from psychology to understand and aid students' practices at a cultural interface

Abstract: The need to address the substantial inequities that exist between Indigenous and non-Indigenous Australians in higher education is widely recognised. Those factors that affect the performance of Indigenous students in tertiary education have been reasonably well documented across different institutions, disciplines, and programme levels but there has, to date, been less consideration of the processes by which Indigenous students either persist or desist in higher education. This paper aims to present a concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Nevertheless, these studies reflect the findings of Krause et al Indigenous students have reported feeling overwhelmed by university, which they find to be an alien and isolating environment, 98 with the stress of navigating an unfamiliar environment being the main reason for withdrawal. 99 Feelings of unfamiliarity are exacerbated by the lack of information for enrolling Indigenous students on university websites, and what is available is often difficult to locate. 100 Enrolment packs and mainstream orientation programmes also lack information for Indigenous students.…”
Section: Barriers To Completing Law Schoolmentioning
confidence: 99%
“…Nevertheless, these studies reflect the findings of Krause et al Indigenous students have reported feeling overwhelmed by university, which they find to be an alien and isolating environment, 98 with the stress of navigating an unfamiliar environment being the main reason for withdrawal. 99 Feelings of unfamiliarity are exacerbated by the lack of information for enrolling Indigenous students on university websites, and what is available is often difficult to locate. 100 Enrolment packs and mainstream orientation programmes also lack information for Indigenous students.…”
Section: Barriers To Completing Law Schoolmentioning
confidence: 99%
“…While it has been widely recognised that Indigenous Australians are significantly under-represented across the higher education sector 1 (Bunda et al., 2012; Day et al., 2015; Hogarth, 2017; Rigney, 2010, 2011; Trewin & Madden, 2005; Trudgett, 2009, 2013), Page et al. (2017) reported that the number of Indigenous students in higher education settings and senior Indigenous staff employed by Australian universities has steadily increased.…”
Section: Introductionmentioning
confidence: 99%
“…Madden [167], C. K. Lemley, T. L. Lee [13], A. Pryor, P. Bowman [21], A. Day, V. Nakata, M. Nakata, G. Martin [4].…”
Section: Introductionmentioning
confidence: 99%